PENGARUH PENDIDIKAN ETIKA BISNIS DAN RELIGIUSITAS TERHADAP PERSEPSI ETIS MAHASISWA AKUNTANSI PADA PERGURUAN TINGGI YOGYAKARTA - Rene Deckhartez Larinda; Putriana Kristanti (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This study aims to determine how business ethics education and religiosity influence the ethical perceptions of accounting students. The study was conducted using a quantitative approach through the distribution of questionnaires to accounting students from three universities in Yogyakarta, namely Duta Wacana Christian University, Atma Jaya University, and Sanata Dharma University. The sample was determined using purposive sampling, resulting in 101 samples. The analysis used was multiple linear regression, descriptive statistics, classical assumption tests, and hypothesis testing. The findings of this study indicate that business ethics education has a positive and significant influence on the ethical perceptions of accounting students. Meanwhile, religiosity also showed a positive and significant influence on the ethical perceptions of accounting students. The results of this study reinforce the view that formal education and spiritual values play an important role in shaping the ethical perceptions of accounting students.